Mentoring for employability: a state-level impact study. (14th October 2019) - Jackson, Claire; Milos, Dani; Kerr, Monica
Abstract : Purpose: Industry mentoring has been repeatedly called out in sector reports on research training in Australian Universities as an effective way to develop PhD capacity and capabilities during research degrees (ACOLA, 2016; NOUS, 2017). Despite the understood importance of this type of experiential development, there is little published evidence on how effective mentoring is to develop the capabilities linked to improved employability. The University of South Australia developed the industry mentoring network in STEM (IMNIS) Impact Evaluation Instrument (IIEI) to capture advanced self-assessed data from mentees and demonstrate what impact the IMNIS program has on developing industry-relevant knowledge and skills in PhD participants. In 2017, the three universities in South Australia implemented a state-wide study using the IIEI to understand the impact of the national IMNIS scheme on the South Australian cohort. Design/methodology/approach: This paper presents a case study on the impact of mentoring on PhD students during the IMNIS program. A self-assessed, competency-based study design has been used to collect pre, mid and post experience data, which measures the extent to which objectives of the IMNIS program are met. The evaluation of the results, using the Vitae Impact Framework (Vitae, 2012), seeks to understand the development of mentees' skills and knowledge as a result of their mentoring experience to support program development and build an evidence base of impact. Findings: This paper presents the 2017/2018 results from the South Australian IMNIS impact evaluation. Through analysis of the three data sets, findings show that skills and knowledge have been developed in mentees as a result of the program. Originality/value: This study provides an extended approach to the existing evaluation undertaken in the national IMNIS program. The IIEI is now available for other universities to use as a method for extended evaluation of their IMNIS program or potentially other WIL opportunities, providing an opportunity for institutional and national benchmarking.